Cities at the Center of the Islamic Intellectual Movement: Mecca, Medina, Kufa, Baghdad, Egypt, and al-Andalus - Fadliana, Nyayu Afriyani Nur; Ismail, Fajri; Ismail, Ismail; Zuhdiyah, Zuhdiyah (The Future of Education Journal, 2025)
This study aims to examine the role and contribution of the cities of Mecca, Medina, Kufa, Baghdad, Egypt, Andalus as centers for the development of Islamic science, education, and culture from the early days to the heyday of Islamic civilization. The research method used is qualitative with a library research approach. Data collection techniques by understanding and studying the theories of various literatures related to the literature such as books, journals and reviews that have been done. The results of the study show that the cities of Mecca, Medina, Kufa, Baghdad, Egypt and Andalus formed an interconnected intellectual network and contributed greatly to the development of Islamic science, philosophy, theology, and education and became centers of learning and development of science that enriched Islamic civilization globally and became a source of inspiration for the development of Islamic intellectuals in various regions, including the Archipelago.